PENINGKATAN KESUBURAN TANAH DENGAN PEMBERIAN PUPUK KOTORAN BURUNG PUYUH DAN POC LIMBAH SAYURAN PADA STEK TANAMAN ANGGUR (Vitis vinifera) DI PRE NURSERY - Dwifa, Nabilah; Tarigan, Ruth Riah Ate; Refnizuida, Refnizuida (Fakultas Pertanian, Universitas Janabadra, 2024)
The aim of this research is to determine the application of quail manure fertilizer and vegetable waste POC in increasing soil fertility on grape plant cuttings (vitis vinifera) in the pre-nursery and their interactions. This research used a factorial randomized block design (RAK) consisting of 2 factors with 12 treatment combinations and 3 replications so that 36 plots were needed in the study. The factor studied was the treatment of quail manure fertilizer which consisted of N0= 0 g/plot, N1 = 400 g/plot, N2 = 800 g/plot, N3 = 1200 g/plot. Factor II treatment of giving POC vegetable waste consists of A0 = 0 mL/liter of water/plot, A1 = 5 mL/liter of water/plot, A2 = 10 mL/liter of water/plot. The parameters observed are plant height, length of tendrils, number of leaves, number of stem segments, stem diameter and number of tendrils. The results of the research showed that the application of quail droppings showed no significant effect on the parameters namely plant height, vine length and stem diameter but had a significant effect on the treatment of the number of leaves, number of stem segments and number of vines. The provision of POC vegetable waste showed no significant effect on plant height, tendril length, number of stem segments, stem diameter and number of tendrils. But it has a real effect on the number of leaves. Key words: planting media, eggshell liquid organic fertilizer, grape plants INTISARITujuan penelitian ini adalah untuk mengetahui pemberian pupuk kotoran burung puyuh dan POC limbah Sayuran dalam peningkatan kesuburan tanah pada stek tanaman anggur (vitis vinifera) di pre nursery berserta interaksinya. Penelitian ini menggunakan Rancangan Acak Kelompok (RAK) Faktorial terdiri dari 2 faktor dengan 12 kombinasi perlakuan dan 3 ulangan sehingga diperlukan 36 plot dalam penelitian. Faktor yang diteliti adalah perlakuan pupuk kotoran burung puyuh yang terdiri dari N0= 0 g/ plot, N1 = 400 g /plot, N2 = 800 g/plot, N3 = 1200 g /plot. Faktor II perlakuan pemberian POC limbah sayuran terdiri dari A0 = 0 mL/liter air/Plot, A1 = 5 mL/liter air/plot, A2 = 10 mL/liter air/plot. Adapun parameter yang diamatin adalah Tinggi Tanaman, panjang sulur, jumlah daun, jumlah ruas batang, diameter batang dan jumlah sulur. Hasil penelitian menunjukan bahwa pemberian pupuk kotoran burung puyuh menunjukan pengaruh yang tidak nyata pada parameter yaitu Tinggi Tanaman, panjang sulur, dan diameter batang tetapi berpengaruh nyata pada perlakuan jumlah daun, jumlah ruas batang, dan jumlah sulur. Pemberian POC limbah sayuran menunjukan pengaruh yang tidak nyata pada Tinggi Tanaman, panjang sulur, jumlah ruas batang, diameter batang dan jumlah sulur. Tetapi berpengaruh nyata pada pelakuan jumlah daun. Kata kunci: media tanam, pupuk organik cair cangkang telur, tanaman anggur